Design, fabrication and experimental study of a novel loop-heat-pipe based solar thermal facade water heating system - Xu, Peng; Shen, Jingchun; Zhang, Xingxing; He, Wei; Zhao, Xudong (Elsevier, 2015)
This paper investigated a novel loop-heat-pipe based solar thermal facade heat-pump system for hot water from concept design, prototype fabrication and experimental test. Given the specific testing conditions, the solar thermal efficiency of the facade module achieved nearly 0.71 in average and the mean system's COP was about 5.0. It is expected that such novel LHP based solar thermal facade technology would further contributed to the development of the renewable (solar) driven heating/hot water service and therefore lead to significant environmental benefits.